1973
DOI: 10.1136/jnnp.36.4.684
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline in migraine prophylaxis: Changes in pattern of attacks during a controlled clinical trial

Abstract: SUMMARY A double-blind controlled clinical trial of crossover design was conducted in 26 volunteers suffering from migraine. Of 20 subjects who completed the trial, 16 had fewer attacks on amitriptyline than on placebo. Amitriptyline was found to have the greatest effect in reducing attacks with a short warning and in which no specific cause could be recognized. It had least effect in attacks with a long warning and recognized as due to fatigue. The drug was effective only in reducing those attacks with shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
5

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(73 citation statements)
references
References 17 publications
1
67
0
5
Order By: Relevance
“…In addition to reducing the frequency, duration and intensity of headache attacks, therapy with amitriptyline may improve the response to acute treatment, reduce disability, and reduce associated economic costs 7,8 . The use of amitriptyline for treatment of migraine resulted in 50% reduction in the headache frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reducing the frequency, duration and intensity of headache attacks, therapy with amitriptyline may improve the response to acute treatment, reduce disability, and reduce associated economic costs 7,8 . The use of amitriptyline for treatment of migraine resulted in 50% reduction in the headache frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with amitriptyline demonstrate limited evidence that the treatment may be beneficial for patients with chronic migraine 14 . Although several studies addressing prophylactic treatment for episodic migraine 6,7,8,9,10,11,12,13,14 , only topiramate 15 and the botulinum toxin 16 were effective in placebo-controlled studies for the prophylactic treatment of patients with chronic migraine.…”
Section: Introductionmentioning
confidence: 99%
“…A large study by Lance & Curran (1964) demonstrated that an antidepressant (amitriptyline) was the drug of choice for tension headaches, and other studies have shown its value as a prophylactic agent for migraine (Couch et a/., 1976;Gommersal & Stuart, 1973). However, the findings of Lance & Curran implied that antidepressants alleviated headaches independently of their antidepressant action.…”
mentioning
confidence: 99%
“…Although few studies [17,18] have provided evidence for a high efficacy of amitriptyline in migraine, this classical tricyclic antidepressant seems to be effective in the prophylaxis of both migraine and chronic TTH [19][20][21][22][23][24][25].…”
Section: Inclusion Criteriamentioning
confidence: 99%